Czy to jest przyjaźń czy to jest kochanie? Związki jednopłciowe a antyczna wizja przyjaźni w kontekście współczesnych dyskusji nad relacją Auzoniusz - Paulin z Noli - Sulpicjusz Sewer - Wysocki, Marcin (Vox Patrum, 2025)
Various studies have suggested homosexual relationships between Ausonius, Paulinus of Nola and Sulpicius Severus. However, based on an analysis of the content and form of their surviving writings, the anthropological views they express, and their approach to homosexuality in ancient Roman culture, such claims should be rejected. Existing sources do not suggest such relationships, and the conclusions are based on a superficial and selective interpretation of the sources. Erotic references and expressions of longing in the letters are literary conventions and games, while the profound relationships described are believed to be ordinary human relationships between students, teachers and friends. Such relationships are depicted in literary works through rhetorical devices that are underpinned by a Christian understanding of friendship and love.